Assessment of Self-care Among Elderly Residents at Nursing Homes in Middle Euphrates Cities in Iraq - Bashaer Mohsen Ali; Ali Kareem Al-Juboori (Indian Journal of Forensic Medicine & Toxicology, 2021)
Self-care is known to be a health resource in later life because it enables the elderly to improve theirhealth and live at home as long as possible(1). It is therefore essential to resolve the question of self-care inthe elderly(2). The aim of the current study was to assess the level of self-care among elderly residents atnursing homes and to find out the difference between level of self-care with regard to socio-demographicand clinical characteristics. Descriptive study design carried out among 60 elderly persons at nursing homesin middle Euphrates, they are selected by using non probability sampling. The study instrument composed of2 parts. 1st Elderly’s Demographic Characteristics, 2nd self-care scale. The results of study reveal the overallassessment of self-care domains was moderate. In addition, there is a high significant in difference in selfcarelevel of the elderly with regard to their age and their marital status.